The influence of supplier partnership in the new product development process: a literature review - Sarges, Simone Ribeiro (2014)
From the literature review of studies addressing issues related to the participation and influence of suppliers in the new product development process, several key themes which affect the issue under study are identified and detailed, highlighting the factors that contribute to the better or worse performance of these partnerships. The intention is to clarify the main problems and the main issues that have guided research concerning this specific and important form of collaboration. This study is, as such, a synthesis of the literature. The main research themes that were identified related to supplier involvement in NPD are the choice of the supplier, the quality of the partnership and the issue of integration. This study also presents the main proposals, extracted from the literature, for lines of future research.